BAGI HASIL TANAH PERTANIAN (MUZARA’AH) (Analisis Syariah dan Hukum Nasional) - Abdullah, Muhammad Ruslan (Al-Amwal : Journal of Islamic Economic Law, 2017)
Profit sharing of agriculture in the economy of Islam known as muzara'ah and Mukhabarah and the results of the agricultural land has been set in law No. 2 of 1960. The profit sharing arrangement is an agreement or a common bond in conducting business activities. In the business agreement for sharing of benefits to be obtained between the two sides or more. Islamic economics and regulations governing the sharing agreement will have a positive impact on the practice of revenue sharing in society